‘Suddenly a Stranger Appears’: Walter Benjamin’s Readings of Bertolt Brecht’s Epic Theatre - Rokem, Freddie (Nordic Theatre Studies, 2019)
My contribution to the the NTS issue on Theatre and Continental Philosophy discusses a particular aspect of the complex intellectual and creative dialogue between the work and thinking of Walter Benjamin and Bertolt Brecht, beginning in 1929, the year they became close friends. Benjamin is no doubt the first critic of Brecht’s epic theatre, even planning to write a book about his artistic contributions. By examining the notion of the “Interruption” (Die Unterbrechung) and the sudden appearance of a stranger in three of Benjamin’s texts about Brecht’s epic theatre, I want to draw attention to Benjamin’s philosophical understanding of this ‘critical’ figure’ (the interrupting stranger), as one of the central aspects of the epic theatre. The essay is a prolegomenon for a more comprehensive study of this topic.